(untitled) (Medico Legal Update, 2021)
Objective: This study was planned to synthesizea novel green Zirconium nanoparticles (ZrNPs), from lemon/and lemon peel with zirconium salt and test its bioactivity against free radicals, and certain cancer cell lines (MCF-7).Materials and Method: Lemon/peel extracts were prepared, mixedwith water and heated to 80 °C, and filtered. The zirconium nanoparticles were synthesized using (ZrCl3) solution which was added to the filtrate (juice and peel) in 1:1 proportion, and UV-Visible was taken. Different concentrations were prepared to study their activity. DPPH assay against free radicals and cytotoxicity against MCF-7 cell line were measured. Results: UV-Visible absorbance of lemon peel/and lemon NPs was carried out and it was found that NPs gave peaks at 457 and 478 nm, while lemon NPs gave peak at 217, and 270 nm. antioxidant activity of all the solutions were carried out, it was found that the peel and juice nanoparticles gave the highest scavenging activity % in all concentrations at 800, 600, 400, and 200 µg/ml which were 93, 78, 57, and 20% respectively. The activity against MCF-7 cancer cell line, the highest inhibition percentage effect (95.16) showed by NPs + Peel, while the lowest effect was 18.42. Conclusion: Novel NPs were synthesized form ZrCl3 and lemon extract/and lemon peel, it was found that the last one is more active against free radical and MCF-7 cell line.